Effect of interval training and drinking vital water on anaerobic capacity, functional indicators and some skills in volleyball - Issa, Samah Nooruldeen (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary objective of this study was to identify the effect of interval training and drinking vital water on anaerobic capacity, functional indicators and some skills in volleyball. The present study had an experimental design of parallel groups, in which participants were divided in two groups: experimental group and control group. The students of the College of Physical Education and Sports Science of the University of Baghdad represented the research community. The participants were selected in a deliberate way. A total of 230 students were present in the research community, of which 20 participants were randomly selected as the sample of the study. All the participants were equally allocated into the two groups, with n=10 in each group. The findings showed that the combination of interval training and drinking vital water had a positive effect on anaerobic capacity, functional indicators and some skills in volleyball.